Rediscovery and lectotypification of Croton claussenianus (Euphorbiaceae), an enigmatic endemic species from southeastern Brazil - Rossine, Yuri; Melo, André Laurênio De; Athiê-Souza, Sarah Maria; de Sales, Margareth Ferreira (Phytotaxa, 2020)
Croton claussenianus was rediscovered after a lapse of 156 years in the same state (Minas Gerais, Brazil) where the type was collected. A description, first illustration, distribution, phenology, and the conservation status of C. claussenianus are provided here; its typification, sectional placement, and relationships are discussed. An identification key to C. claussenianus and its closest relatives in Minas Gerais State is also provided.